2016
DOI: 10.1002/hbm.23474
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive phenotypes in parkinson's disease differ in terms of brain‐network organization and connectivity

Abstract: Cognitive deficits are common in Parkinson's disease and we suspect that dysfunctions of connected brain regions can be the source of these deficits. The aim of the present study was to investigate changes in whole-brain intrinsic functional connectivity according to differences in cognitive profiles in Parkinson's disease. 119 participants were enrolled and divided into four groups according to their cognitive phenotypes (determined by a cluster analysis): (i) 31 cognitively intact patients (G1), (ii) 31 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 70 publications
9
69
2
Order By: Relevance
“…Indeed, it was found that the global connectivity measurement explained a significant proportion of the variability in the network connectivity metrics, such that the SMN remained the only network which had independently decreased connectivity. Global alterations in brain organization have been observed, with increased randomness being associated with worsening cognitive function . These results suggest that in addition to network targeted degeneration, there may also be a less constrained degenerative process occurring.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it was found that the global connectivity measurement explained a significant proportion of the variability in the network connectivity metrics, such that the SMN remained the only network which had independently decreased connectivity. Global alterations in brain organization have been observed, with increased randomness being associated with worsening cognitive function . These results suggest that in addition to network targeted degeneration, there may also be a less constrained degenerative process occurring.…”
Section: Discussionmentioning
confidence: 96%
“…With this approach, anatomic brain regions are considered to be nodes, linked by edges, which represent the connectivity measured by the temporal correlation of BOLD fluctuations between the nodes. To date, only a few RS-fMRI studies using graph theoretical approach have been conducted in patients with PD [24][25][26][27][28][29][30][31] with a degree of inconsistency between studies mostly related to the small number of subjects or the inclusion of subjects across different PD stages.…”
Section: Introductionmentioning
confidence: 99%
“…9 This was subsequently confirmed in a cross-sectional study. 9,10 Moreover, we showed that the identified clusters were associated with different patterns of functional connectivity using functional Magnetic Resonance Imaging (fMRI) 11 and highdensity-EEG. 12 However, the identification of these different levels of cognitive deficits with easily available markers is needed.…”
mentioning
confidence: 96%